2014
DOI: 10.1371/journal.pone.0113579
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Hepatitis C Virus Infection Is Associated with the Development of Rheumatoid Arthritis: A Nationwide Population-Based Study in Taiwan

Abstract: ObjectiveThe association between chronic hepatitis virus infection and rheumatoid arthritis (RA) remains debatable. This nationwide population-based cohort study assessed the risk of RA among patients with a chronic infection of hepatitis B and/or C virus.Materials and MethodsWe used data extracted from the claims of 1,000,000 randomly sampled individuals covered under the Taiwan National Health Insurance program. Among the 49,892 persons identified in 2000–2010 with chronic hepatitis virus infection, 35,652 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
(35 reference statements)
0
20
0
2
Order By: Relevance
“…Five studies were identified which evaluated the risk of developing rheumatoid arthritis in HCV‐infected patients (N = 18 234); three of those studies also included a control group . Two studies were from Japan, one study was from Korea, and two from Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were identified which evaluated the risk of developing rheumatoid arthritis in HCV‐infected patients (N = 18 234); three of those studies also included a control group . Two studies were from Japan, one study was from Korea, and two from Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…This high rate of RF seropositivity in patients with chronic HCV infection presents diagnostic and therapeutic difficulties for the clinician. In addition, one nationwide population‐based study in Taiwan revealed that chronic HCV infection is associated with RA development . Therefore, the presence of RF is of little value in distinguishing between RA and HCV‐associated arthritis, especially because a high‐positive RF level is given a score of 3 in the 2010 classification criteria for RA.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, anti-citrullinated protein antibody could ensure enhanced clinical significance in implementation in clinical diagnosis of rheumatoid arthritis in the current and previously similar research studies [2,6] In great harmony with the current research study results a prior research has shown that female study subjects revealed a greater prevalence of positive rheumatoid factor. This could be justified in correlation to gender-sex hormonal serum levels that could trigger autoantibodies production [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some illnesses e.g. chronic hepatitis C virus infection can clinically present with an extrahepatic symptom and signs profile mimicking rheumatoid arthritis [3,4].…”
Section: Introductionmentioning
confidence: 99%